Effects of strength training with eccentric overload on muscle adaptation in male athletes - Friedmann-Bette, B.; Bauer, T.; Kinscherf, R.; Vorwald, S.; Klute, K.; Bischoff, D.; Müller, H.; Weber, A. A.; Metz, J.; Kauczor, H. -U.; Bärtsch, P.; Billeter, R. (European Journal of Applied Physiology, 2010)
In classic concentric/eccentric exercise, the same absolute load is applied in concentric and eccentric actions, which infers a smaller relative eccentric load. We compared the effects of 6 weeks of classic concentric/eccentric quadriceps strength training (CON/ECC, 11 subjects) to eccentric overload training (CON/ECC+, 14 subjects) in athletes accustomed to regular strength training. The parameters determined included functional tests, quadriceps and fibre cross-sectional area (CSA), fibre type distribution by ATPase staining, localisation of myosin heavy chain (MHC) isoform mRNAs by situ hybridization and the steady-state levels of 48 marker mRNAs (RT-PCR) in vastus lateralis biopsies taken before and after training. Both training forms had anabolic effects with significant increases in quadriceps CSA, maximal strength, ribosomal RNA content and the levels of mRNAs involved in growth and regeneration. Only the CON/ECC+ training led to significantly increased height in a squat jump test. This was accompanied by significant increases in IIX fibre CSA, in the percentage of type IIA fibres expressing MHC IIx mRNA, in the level of mRNAs preferentially expressed in fast, glycolytic fibres, and in post-exercise capillary lactate. The enhanced eccentric load apparently led to a subtly faster gene expression pattern and induced a shift towards a faster muscle phenotype plus associated adaptations that make a muscle better suited for fast, explosive movements.